Proposing a model of critical literacy program for fostering Indonesian EFL students’ critical thinking skills - Nia Kurniawati; Deuis Sugaryamah; Aan Hasanah (Journal of Education and Learning (EduLearn), 2020)
This study was intended to depict how Critical Literacy Pedagogy (CLP) principles were incorporated in EFL reading class in Indonesian secondary school and the students’ Critical Thinking (CT) were fostered during learning process.  This study was a classroom practice-based model of how the principles were transferred into the detailed teaching syntax in an Islamic senior high school in West Java Indonesia.  As a case study elaborating how a phenomenon happened, this study explored teaching steps, teacher-students dialogues, questions and the way the questions posed reflecting students’ CT skills, and students’ engagement in the learning process. The use of Indonesian folklores containing controversy predicted to enable students develop their thinking skills became novelty of the study. In addition, three times interventions were designed in which each intervention consisted of (a) teaching critical thinking concept explicitly and implicitly, (b) seven steps of teaching reading procedure incorporating CLP principles (explaining author’s purpose, activating students’ prior knowledge, reading text loudly, discussing text in group, exploring the text in class activities in which Critical Literacy Questions and CT Questions are incorporated, answering comprehension questions in group, and reflection, and (c) CT skills discussion. This study provides an alternative model of teaching CT in Indonesia context.